Effect of agroforestry woody species on earthwarm activities and physicochemical properties of warm casts - Kang, B.; Akinnifesi, F.K.; Pleysier, J.L. (1994)
The effects of five agroforestry woody species (Dactyladenia barteri, Gliricidia sepium, Leucaena leucocephala, Senna siamea andTreculia africana) on the surface aasting activity ofHyperiodrilus africanus were studied in an Alfisol (Oxic Paleustalf) in southwestern Nigeria. Casting activity under the woody species decreased in the following order:Dactyladenia sp. (26.4 Mg ha-1 year-1)>Gliricidia sp. (24.4 Mg ha-1 year-1)>Treculia sp. (22.9 Mg ha-1 year-1)>Leucaena sp. (18.6 Mg ha-1 year-1)>Senna sp. (18.3 Mg ha-1 year-1). These differences in casting activity were partly explained by microclimatic effects. Irrespective of the woody species, the worm casts were higher in clay and silt contents, bulk density, water-stable aggregates, pH, organic C, exchangeable cations, effective cation exchange capacity, and extractable P levels than the corresponding surface soils. The woody species did affect the physicochemical properties and P sorption of the worm casts. The content of water-stable aggregates of worm casts decreased in the following order:Dactyladenia sp.>Treculia sp.>Senna sp.>Leucaena sp.>Gliricidia sp. Large differences in extractable P levels were observed.Senna sp. was associated with the highest extractable P level (11.5 mg kg-1) andTreculia sp. the lowest (4.9 mg kg-1). P sorption was highest on worm casts underDactyladenia sp. and lowest on those underTreculia sp. Without fertilizer application, there were no significant differences in the dry weight of maize grown in the different worm casts. With NPK applications, the dry weight of maize grown in worm casts associated withTreculia sp. was significantly lower than that of maize grown in the other worm casts, mainly due to the low extractable P level. Despite a high organic C and exchangeable K status, maize grown in the worm casts still responded significantly to N and K applications. The N uptake by maize grown in worm casts associated withTreculia sp. was lower than that in the other treatments.